The Eight Years of Interaction: Lessons from Zimbabwe’s Look East Policy and the Future of African Countries and Asia-Pacific Region - Chigora, Percyslage; Chisi, Taderera Hebert (Journal of Sustainable Development in Africa, 2020)
The Eastern Asia and Oceanic states have proven to be a hub of technological sophistication that have driven economic growth and subsequently intensified production of goods and service provision. As such, most African countries have forged closer ties with countries in this region and, as a result, there has been reluctance in approaching the West. Zimbabwe, in particular, after receiving unfavourable treatment by the West, developed a new policy of associating with the East. The year 2008 marks eight years of interaction between Zimbabwe and the East, dubbed the Look East Foreign Policy. The policy is intended to discover new acquaintances in the East to enable her development processes. The extent to which it has been successful has been doubted in some circles. Therefore, the paper seeks to review the eight years of Zimbabwe’s interaction with the East, elucidating on the achievements, challenges, and the future of the relations. The paper also seeks to unearth the controversies surrounding the success of both North-South and South-South cooperations. In the final analysis, the paper provides guidance on factors contributing to foreign policy success in developing countries, particularly those in Africa.